Application of SCOR to e-government: a case study. (1st October 2007) - Alvarado, Karla; Rabelo, Luis; Moraga, Reinaldo; Quijada, Sergio; Gruber, Fred; Sepulveda, Jose
The aim of this paper is to introduce a roadmap detailing how to apply the Supply Chain Operations Reference (SCOR) model to e-government to analyse, design and improve supply chain performance. This roadmap arose out of lessons learned from a successful implementation of SCOR in an aerospace company. We validated this roadmap by applying it in three different case studies provided by the Supply Chain Council (SCC). We then implemented this framework roadmap to streamline the service supply chain (using the internet) of the government of Seminole County, Florida. The SCOR framework facilitates simulation by providing a template that can be followed to describe the 'as is' and the 'to be' system.